Teacher Professional Development in Tanzania: Challenges and Opportunities - Komba, Sotco Claudius; Mwakabenga, Rehema Japhet (Educational Leadership, 2019)
This chapter is about teacher professional development in Tanzania. The authors have examined the current status of teacher professional development in Tanzania, focusing on predominant perspectives on the concept and provision modalities. In addition, the authors have identified challenges facing teacher professional development in Tanzania, most of which seem to be systemic. The challenges include lack of explicit policy and guidelines for teacher professional development, limited knowledge on teacher professional development among teacher professional development stakeholders, predominance of traditional approach to teacher professional development, and ineffective organization of teacher professional development activities. It is, thus, concluded that a number of opportunities are available for effective teacher professional development in Tanzania. These include strengthening the available institutions responsible for teacher professional development, making use of different teacher professional development providers available in the country to promote professional development activities for teachers through a harmonized scheme and capitalizing on the use of different communication networks and the national optic fiber to promote self-directed teacher professional development.
Publisher: IntechOpen KerkoCite.ItemAlsoKnownAs: 10.5772/intechopen.90564 2339240:9MJFKUCS 2405685:632GMNKZ
Keywords: _Tanzania; _final_bib

Improving teacher professional development for online and blended learning: a systematic meta-aggregative review - Philipsen, Brent; Tondeur, Jo; Pareja Roblin, Natalie; Vanslambrouck, Silke; Zhu, Chang (Educational Technology Research and Development, 2019)
In order to fully realise the potential of online and blended learning (OBL), teacher professional development (TPD) strategies on how to teach in an online or blended learning environment are needed. While many studies examine the effects of TPD strategies, fewer studies target the specific important components of these strategies. This study addresses that gap by conducting a systematic review of qualitative data consisting of 15 articles on TPD that targets OBL. Using a meta-aggregative approach, six different synthesised findings were identified and integrated into a visual framework of the key components of TPD for OBL. These synthesised findings are the base for the action recommendations which present specific and contextualised suggestions. Taken together, the findings can inform in-service teachers and trainers, together with further research and development efforts that are concerned with TPD for OBL.
Extra URL: https://doi.org/10.1007/s11423-019-09645-8 KerkoCite.ItemAlsoKnownAs: 10.1007/s11423-019-09645-8 2405685:BVQU5XV8 2534378:4WR2J4Z5

The Influence of Teachers’ Professional Development Activities on the Factors Promoting ICT Integration in Primary Schools in Mongolia - Li, Shengru; Yamaguchi, Shinobu; Sukhbaatar, Javzan; Takada, Jun-ichi (Education Sciences, 2019)
This paper examines the influences of professional development activities on important teacher-level factors that are important for the use of Information and Communication Technology (ICT) in education for primary school teachers in Mongolia. The study utilizes the survey data collected in 2012 (n = 826) and 2016 (n = 1161) to identify the changes in factors that are important to the use of ICT in education. The study result shows that six teacher level factors that are important for the ICT integration have been improved over time through professional development activities. These are professional competency in educational use of ICT, collaboration for ICT integration, benefits on use of ICT, autonomy to innovate, recognition as a professional, and skills and practices in educational use of ICT. This provides supporting evidence to educational practitioners for the implementation of effective professional development programs to promote ICT integration in education, especially in the developing country’s context.
Number: 2 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/educsci9020078 2339240:XWWZXZ76 2405685:EENQXYD4
Keywords: ICT in education; ___working_potential_duplicate; auto_merged; education policy; educational change; factors promoting ICT integration; teacher’s professional development

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement - Kennedy, Eileen; Laurillard, Diana (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.
Publisher: UCL IOE Press shortDOI: 10/gg39w8 KerkoCite.ItemAlsoKnownAs: 10.18546/LRE.17.2.04 10.18546/lre.17.2.04 10/gg39w8 2339240:8UKVPWIZ 2339240:HI8ZPSQY 2339240:IQ8CXXW6 2405685:BPEFU8Q5 2405685:G4UWRHU7 2405685:HZVTXVSX 2534378:G73NNFJ5 2534378:SB3A7XEN 2534378:XASAZC2M
Keywords: BLENDED learning; CO DESIGN MOOCS REFUGEES TEACHERS THEORY OF CHANGE; DIGITAL technology; Design; Digital technology; Education; Google Scholar/ "blended learning" refugee education; Lebanon; MASSIVE open online courses; MOOCs; Online instruction; PROFESSIONAL education; Professional development; RER theme_supporting educators; TEACHER development; __:import:01; __:match:final; __:matched; __:study_id:2095772; ___working_potential_duplicate; __finaldtb; co-design; refugees; teachers; theory of change

Examining sustained impacts of two teacher professional development programs on professional well-being and classroom practices - Wolf, Sharon; Peele, Morgan E. (Teaching and Teacher Education, 2019)
We examine second-year impacts of a 1-year pre-primary teacher training and coaching program, delivered with and without parental-awareness meetings, evaluated with a school-level randomized trial. Outcomes included teachers’ professional well-being and classroom practices. Most gains observed during the program year faded out. However, there were small sustained impacts on the implementation of training activities. Counteracting effects of the parental-awareness meetings were evident, with suggestive evidence that teachers in this treatment group displayed lower scores on one dimension of classroom qualitydSupporting Student Expressiondcompared to controls. Implications for professional development and educational quality are discussed.
shortDOI: 10/ggjk6c KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2019.07.003 10/ggjk6c 2339240:GB3MPNJU 2405685:M8ZR3GRF
Keywords: _proposed-for: Scoping review

Pakistani Teacher-Educator Professional Learning through an International Blended Course - Impedovo, Maria Antonietta; Malik, Sufiana Khatoon (Open Praxis, 2019)
International teacher-educator learning supports a more complex vision of teacher professionalism for both developed and developing countries. The aim of this paper is the analysis of Pakistani teacher-educator professional learning after attending an international blended course, considering the impact of online and face-to-face participation and the main competencies involved in their professional learning. The blended learning course attended by the Pakistani Teacher-educators is part of an international project between Europe and Asia. The analysis is carried out using written traces in the online platform; 47 questionnaires at the end of the face-to-face training sessions in Pakistan and 10 deep-interviews with Pakistani educators; the written traces, open questions, and deep-interviews were qualitatively analyzed. Additionally, the educators' technological, pedagogical and instructional design and interpersonal and intercultural skills were also analysed. The paper considers how international learning could affect the professional learning of teacher-educators in Global South and the centrality of the design of innovative learning courses for today's environment of international globalization.
Publisher: International Council for Open and Distance Education KerkoCite.ItemAlsoKnownAs: 10.5944/openpraxis.11.2.928 2339240:YNGS2RBD 2405685:DLCJJKLI
Keywords: Blended Learning; Cultural Awareness; Faculty Development; Foreign Countries; Instructional Design; International Education; Interpersonal Competence; Professionalism; Skill Development; Teacher Educator Education; Teacher Educators; Teaching Skills; Technological Literacy

Developing TPACK in science and mathematics teacher education in Tanzania: A proof of concept study - Kafyulilo, Ayoub; Fisser, Petra (Collaborative Curriculum Design for Sustainable Innovation and Teacher Learning, 2019)
Since 1997, the government of Tanzania has made several attempts at introducing technology into education. However, despite these efforts technology has not become integrated into educational practice. A main reason is that teachers do not embrace the use of technology in their teaching. This study was initiated to design, implement and evaluate a professional development arrangement aimed at promoting teachers’ use of technology in their teaching practice. The study started with a ‘proof of concept’ study. Based on experiences in Ghana and Kuwait, a professional development arrangement was developed that incorporated ‘learning technology by design’ to prepare pre-service science and math teachers for using technology in their teaching. The experiences from this study informed the design of a professional development arrangement for practicing science teachers. The iterative design, implementation and evaluation of the professional development arrangements will be presented and discussed.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-20062-6_8 2339240:MQPLNUJN 2405685:Z8QTSILA

Reforming teacher education in Nigeria: Laying a foundation for the future - Barnes, Adrienne E.; Boyle, Helen; Zuilkowski, Stephanie Simmons; Bello, Zaliha Nasiruddeen (Teaching and Teacher Education, 2019)
Teacher educators in Nigeria receive limited professional development, particularly regarding the instruction of early grade reading skills. As part of the USAID-funded Northern Education Initiative Plus project, Florida State University faculty provided intensive teacher educator professional development to staff at four Teacher Education Institutions in northern Nigeria. Positive impacts on teacher educator knowledge, skills, and attitudes were observed related to content and pedagogical knowledge, use of participatory teaching and learning activities in the college classrooms, and improvement in student teacher engagement and learning. Continued success of the implemented model for training will be dependent upon national adoption and scale up.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2018.12.017 2339240:982EMD2L 2405685:7EPWKCK2

Synthesis of Reviews on Teacher Professional Development in Sub-Saharan Africa - Haßler, Björn; D’Angelo, Sophia; Walker, Hannah; Marsden, Melissa (Open Development & Education, 2019)
EdTechHub.Source: 2129771:SC8FTPC4 KerkoCite.ItemAlsoKnownAs: 2129771:SC8FTPC4 2339240:GJ83JMQA 2405685:T7DTBWJB
Keywords: _yl:i; dode_eth-src-dode; dode_eth-trf2-dode

Broadening borders to build better schools: virtual professional learning communities - Carpenter, Daniel; Munshower, Paul (The International Journal of Educational Management, 2019)
PurposeThe purpose of this paper is to explore how rural teachers provided a PLC by leveraging virtual technologies to connect educators of like subject disciplines from several schools, foreign and domestic.Design/methodology/approachA phenomenological case study-based approach was leveraged to investigate established vPLCs at schools (Creswell, 2013; Stake, 2010). Qualitative data were collected from multiple sources to obtain rural teacher perceptions on the impact vPLCs had on their practice (Creswell, 2013).FindingsTeacher collaborative teams build relationships comparable to teams that met face to face as part of a similar PLC and PD experience. Participant reflections in this investigation showed that rural educators favored face-to-face meetings; however, vPLCs provided similar teacher experiences to that of the face-to-face PBL model. Results indicated that educators recognized virtual collaboration just as valuable a tool for enabling PLCs than face-to-face collaborations while still offering similarities to improved teacher practice.Research limitations/implicationsThe research was limited to teachers in rural settings in the USA (Texas) and in the Dominican Republic. The research was limited to teacher perceptions of change, and observed changes as part of their participation in a research-based virtual PLC model. The research was limited to the school setting over an academic year.Practical implicationsThe findings from this study have practical implications for rural teachers and school implementation of a professional learning community model.Originality/valueThe promise provided by this study is that vPLCs may provide opportunity for rural schools to provide a job-embedded professional development model (Croft et al., 2010) for otherwise isolated teachers (Barrett et al., 2015).
Place: Bradford Publisher: Emerald Group Publishing Limited Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2338030077?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1108/IJEM-09-2018-0296 2339240:ITBNKNJS 2405685:493XEK9T 2405685:BXCJZXC3 2534378:9DM4HQE9 2534378:BDJAHBNX 2534378:EEJ2GZ6E
Keywords: Collaboration; Communities of Practice; Computer Mediated Communication; ERIC; Current Index to Journals in Education (CIJE); Education; Educational technology; Faculty Development; Learning; Meetings; Preferences; Professional development; Professional learning communities; Rural Schools; Rural schools; School districts; Teacher Attitudes; Teacher Collaboration; Teacher collaboration; Teachers; Teaching; Virtual professional learning communities; __:import:01; __:match:final; __:matched; __:study_id:2095794; __finaldtb

Community-Based Teacher Training: Transformation of Sustainable Teacher Empowerment Strategy in Indonesia - Mardapi, Djemari; Herawan, Tutut (Journal of Teacher Education for Sustainability, 2019)
Teacher empowerment is a central issue in relation to the efforts to improve the quality of education. However, teacher empowerment will remain an abstract idea if its implementation is not supported by an appropriate strategy. The demands for a quality education will be unreciprocated if teachers do not have the opportunity to empower themselves. This research aims to investigate the teacher empowerment strategy in Indonesia, which has been conducted by employing a community-based teacher training program. This study has highlighted several research questions: What is meant by community-based training program? Why is the training program needed? Who is the target of the training program? What model has been used to implement the training? What are the results of the training that has been executed? This research was conducted from November 2018 to January 2019. The research data were collected by means of documentation studies and interviews. The data analysis was carried out quantitatively and qualitatively, where the quantitative analysis was processed based on the document study data, meanwhile the qualitative analysis was performed based on the interview data. The research results showed that community-based teacher training was transformation of teacher development strategy as a follow-up on teachers’ competency test in Indonesia. The community-based teacher training succeeded in increasing the professionalism of teachers in Indonesia, particularly in terms of implementing their pedagogical and professional competencies. The training is also successful in motivating the teachers to engage themselves in continuous learning efforts through building strong teachers’ network and working collaboratively with colleagues. Quantitatively, training was proven to increase the average of teacher competency by 23.97 (on a scale of 100). The research results are expected to provide information about the best practice in teacher coaching that is conducted massively in a national scope based on the local community so that a lifelong learning culture for teachers is established to support the development of sustainable education.
KerkoCite.ItemAlsoKnownAs: 10.2478/jtes-2019-0004 2405685:8YANT76F

Technology and Teacher Professional Development (TPD): the Process and Content of Microlearning in a School-Based Integrated In-Service Teacher Education (INSET) Project - Junaid, Muhammad Ibn; Ogange, Betty; Allela, Melisa (Commonwealth of Learning (COL), 2019)
Continuing teacher professional development for all teachers across the entire school system poses a challenge in many contexts, especially in developing countries. Teachers from schools located in remote rural areas usually have fewer professional development opportunities due to the lack of accessibility either to their schools or to professional development resources. On-site school-based professional development is a viable option if innovative design is adapted to generate microlearning resources that teachers can easily access and share. This paper reports on a technology enabled school-based integrated INSET project coordinated by the Freetown Teachers College (FTC) in 12 junior secondary schools (JSS) in Sierra Leone under the COL’s Teacher Futures Programme. The project represents an innovation in TPD and is different from the general type of face-to-face and exclusively paper-based in-service teacher training programme common in Sierra Leone. Under the new project a multimodal approach is used where the FTC mentors and the communities of learners (JSS teachers) are presented with both print and microlearning resources and also provided access to an eLearning platform and the use of mobile phones as the main vehicles of delivery. Microlearning is an emergent learning strategy known for its quick response in bridging skills and knowledge gaps. In the context of the INSET Project, it involves a weekly dose of pedagogical content knowledge and skills, including modelling of classroom best practices which teachers can adapt and use. The project design and methods are briefly described, but the main focus of the paper is on the microlearning component of this project and discusses the use of mobile technology in the delivery and implementation of TPD in the 12 project schools. The emphasis is on the methodological and management challenges that arise in creating and nurturing communities of practice (CoPs) in a school-based setting and how these are addressed by the various schools involved.
KerkoCite.ItemAlsoKnownAs: 2405685:AALEIRC2

Transforming Teacher Education and Learning in Ghana: The Impact of a Continuous Professional Development on Physics Teaching at the Colleges of Education - Coffie, Isaac Sonful (International journal of Research and Scientific Innovation, 2019)
The colleges of education in Ghana have been involved in a continuous professional development for over four years with support of Transforming Teacher Education and Learning (T-TEL). The main purpose of this research was to assess the perceived impact of the continuous professional programme on physics teaching at the colleges of education. Descriptive cross sectional survey was used for the study. An online survey was conducted which was completed by 85 physics tutors. The survey data were analysed using means and standard deviations and ANOVA. It was found that the professional development is perceived by the physics tutors to have great impact on their teaching practice. It was also found out that there was no statistical significant difference in the perceived impact of the professional development based on tutors’ experience. It was concluded that if the student teachers who are being trained by these tutors will learn these ideas from their tutors and practice them, teaching at the basic schools will be more interactive, students-centered and gender responsive.
EdTechHub.ItemAlsoKnownAs: 2405685:IPJBNU3S
Keywords: ⛔ No DOI found

Supporting teachers in taking up productive talk moves: The long road to professional learning at scale - O’Connor, Catherine; Michaels, Sarah (International Journal of Educational Research, 2019)
In this paper we describe our early, qualitative work on “teacher talk moves” such as revoicing, situated within the urban classrooms of highly skilled teachers, including their role in the work of managing multiple constraints while maintaining productive inclusivity. We then describe our attempts to discern the impact of these talk tools on student achievement in multiple classrooms, using both post-hoc controls and in vivo studies. We move on to the challenges present in disseminating this work in professional development settings; our approach includes framing talk tools as rational responses to actual classroom challenges. Finally we describe current efforts to disseminate cyber-enabled PD in science education K-12, including a central focus on academically productive talk.
shortDOI: 10/ghgn5s KerkoCite.ItemAlsoKnownAs: 10/ghgn5s 2405685:X9V64KPT 2534378:LDIGVCHK

Experimental Impacts of the “Quality Preschool for Ghana” Interventions on Teacher Professional Well-being, Classroom Quality, and Children’s School Readiness - Wolf, Sharon; Aber, J. Lawrence; Behrman, Jere R.; Tsinigo, Edward (Journal of Research on Educational Effectiveness, 2019)
We assessed the impacts of a teacher professional development program for public and private kindergartens in the Greater Accra Region of Ghana. We examined impacts on teacher professional well-being, classroom quality, and children’s readiness during one school year. This cluster-randomized trial included 240 schools (teachers N ¼ 444; children N ¼ 3,345, Mage ¼ 5.2) randomly assigned to one of three conditions: teacher training (TT), teacher training plus parental-awareness meetings (TTPA), and controls. The programs incorporated workshops and in-classroom coaching for teachers and video-based discussion groups for parents. Moderate impacts were found on some dimensions of professional well-being (reduced burnout in the TT and TTPA conditions, reduced turnover in the TT condition), classroom quality (increased emotional support/behavior management in the TT and TTPA conditions, support for student expression in the TT condition), and small impacts on multiple domains of children’s school readiness (in the TT condition). The parental-awareness meetings had counteracting effects on child school readiness outcomes. Implications for policy and practice are discussed for Ghana and for early childhood education in low- and middle-income countries.
shortDOI: 10/ggjrcj KerkoCite.ItemAlsoKnownAs: 10.1080/19345747.2018.1517199 10/ggjrcj 2339240:S3WAE3PS 2405685:H52RQ6MY 2405685:JXYTEU3W
Keywords: Ghana; ___working_potential_duplicate; classroom quality; early childhood education; kindergarten; school readiness; teacher training and coaching

Approaches to teacher professional development in low-to-middle-income countries - Power, Tom (Sustainable English language teacher development at scale: Lessons from Bangladesh, 2019)
This chapter begins by situating discussion of approaches to teacher development (TD) in the context of the grand societal challenge of Education for All (UNESCO 2014), as written into the earlier Millennium Development Goals (MDGs) and now Sustainable Development Goal (SDG) 4:‘to ensure inclusive and equitable quality education for all.’ This goal cannot be met without addressing the stark and urgent need for greater numbers of teachers who are adequately equipped with the knowledge and skills to enable effective student learning. Drawing upon personal experiences of work with teachers in LMICs over nearly two decades, the chapter argues against ‘blaming teachers’ for poor student learning outcomes, and advocates instead the development of better understandings of the often challenging contexts in which teachers practise. The chapter then critically examines common approaches to TD that have often failed adequately to equip teachers for classroom practice, outlining a broadly supported agenda for reform. Recent literature has begun to identify certain characteristics of TD programmes that are increasingly associated with effective student outcomes, in what may be an emerging consensus. These characteristics are briefly outlined, before the chapter closes with lessons learned from English in Action. EIA has both contributed to and benefitted from this emerging evidence base and Chapter 5 illustrates how the implementation of EIA exemplifies such characteristics through a cohesive programme design.
Extra URL: http://oro.open.ac.uk/57052/ KerkoCite.ItemAlsoKnownAs: 2339240:D5ABKQWT 2405685:5G9NIHEU 2405685:KJGDVY5F 2405685:P8GU4VUJ 2405685:W9CSF5TT 2534378:3KFFQRC7 2534378:RSWZTN7D
Keywords: Important; Read

Insights on ESL student teachers reflecting collaboratively online - Suppiah, Shubashini; Wah, (PhD), Lee Kean; Swanto, (PhD), Suyansah; Lajium, (PhD), Denis Andrew (The English Teacher, 2019)
The concept of a collaborative based reflective practice approach is grounded within the theoretical argument that critical reflection can be fostered through the presence of the "knowledgeable other" (Vygotsky, 1978). The present study was a pilot initiative in utilizing EDMODO (a closed educational learning management system) as a platform to explore reflection in a communal approach within a group of pre-service ESL teachers and their teacher educator mentor during a teaching practice placement in the context of the TESL (Teaching English as a Second Language) degree programme in an institute of teacher education (ITE) in Malaysia. The aims of the study are: (1) to examine the nature of the online reflection posts; and (2) to explore the nature of interactions that occurred online and the extent it supported collaborative reflection practices. The study employed a qualitative case study design in which five pre-service teachers (n=5) and their teacher educator mentor used EDMODO to post their reflections and carry out discussions for four weeks (n=4). The sources of data were the online reflection posts, the threaded discussion posts and a semi-structured group interview. Despite initial ambiguities and constraints, the EDMODO learning site as a platform for reflective practice showed positive results in that it allowed collaboration and dialogue to take place. Nevertheless, the facilitation of the reflection process requires further inquiry. The findings of the study suggest the need to establish a more systematic and structured approach when fostering critical reflection practices in a communal setting.
Place: Seri Kembangan Publisher: Malaysian English Language Teaching Association (MELTA) KerkoCite.ItemAlsoKnownAs: 2405685:N9ZPHXCW 2534378:DFCJXPJ2 2534378:VI3TK6EI 2534378:VWP4487Z
Keywords: Collaboration; Distance learning; English as a second language–ESL; Linguistics; Malaysia; Problem solving; Professional development; Reflective practice; Researchers; Social research; Student teachers; Teacher education; Teaching; Web 2.0; __:import:01; __:match:final; __:matched; __:study_id:2095770; __finaldtb; ⛔ No DOI found

An exploration of agency in the localisation of open educational resources for teacher development - Wolfenden, Freda; Adinolfi, Lina (Learning, Media and Technology, 2019)
This study examines the practice of adaptation and translation (localisation) of Open Educational Resources (OER). It employs a sociocultural perspective to focus on the experiences of practitioners (localisers) who undertook the localisation of a suite of 125 OER created as part of a teacher professional development programme in India. This localisation process generated eight unique versions of the OER in five languages. Drawing on project reports, practitioner interviews and analysis of the adapted OER, the study explores how localisers created meaning for the task, the situational and linguistic factors that influenced and mediated their decisions to adapt the materials – or not – and the skills and experiences that emerged through the process. Although the findings revealed that changes to the materials were limited, suggesting that enacting localisation is more difficult than perhaps suggested by OER proponents, the analysis indicated forms of localisers’ emerging professional agency through this endeavour.
Publisher: Routledge _eprint: https://doi.org/10.1080/17439884.2019.1628046 Extra URL: https://doi.org/10.1080/17439884.2019.1628046 KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2019.1628046 2405685:D4SI9BWU 2534378:ALXXMXLY 2534378:ZPP9MH8V
Keywords: India; Open educational resources (OER); __:import:01; __:match:final; __:matched; __:study_id:2457357; __finaldtb; localisation; professional agency

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement - Kennedy, E.; Laurillard, D. (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.
Number: 2 Publisher: Taylor & Francis KerkoCite.ItemAlsoKnownAs: 2339240:3R3E5UKD 2405685:IWSGHR2Y

Online teacher professional development in ICT integration in Tanzania: An experience report - Ngeze, Lucian Vumilia; Iyer, Sridhar (Proceedings of the 27th International Conference on Computers in Education., 2019)
Integration of Information and Communication Technology (ICT) in teaching and learning in schools has been hindered by many barriers, including lack of in-service teacher training, teacher beliefs and lack of infrastructure. In the effort to solve the challenge of teacher training in Tanzania, few in-service teachers, based on different parameters, are selected to participate in the face to face ICT training at the specified training centre. Scaling of such teacher training initiatives has been challenging over time. To reach more school teachers, we developed a ten-day online course, run over Moodle. A total of 134 teachers from all the regions of Tanzania registered and participated. Topics were developed based on the preference of the in-service teachers. Online surveys were used to collect qualitative and quantitative data before and after the course. Teachers were active during the duration of the course and many of them applied the skills in their schools by improving their teaching strategies, use of technology tools and sharing experiences with other teachers in their schools.
KerkoCite.ItemAlsoKnownAs: 2339240:ADH54AWX 2405685:DEL3AXBD
Keywords: ⛔ No DOI found

Using design-based research to bring partnership between researchers and practitioners - Getenet, Seyum (Educational Research, 2019)
Background: A key aim of educational research is for findings to inform practice, thereby bringing about improvements in teaching and learning. However, the relationship between research and practice is complex, and there is often no clear link between changes in practice and research findings. One of the challenges for research and practice is breaking down barriers and finding effective and sustainable ways to translate research findings into practical solutions in the classroom.Purpose: This discursive paper focuses on describing the nature of the partnership working involved when a design-based research (DBR) approach was employed to bring researchers and practitioners together. The researchers and practitioners worked in collaboration to design a professional development (PD) programme, in order to solve classroom problems and enhance practitioners’ research engagement.Sources of evidence: This paper describes the author’s experience of using DBR to co-design a PD programme that was responsive to a particular context and practitioners’ needs. It illustrates and exemplifies the ways in which the researcher–practitioner collaboration itself sits at the heart of the design process and enabled solutions to be found. The paper also considers the epistemological positions of the practitioners and researchers in the different stages of DBR. The context for the description is a mixed-methods intervention study conducted in two colleges of teacher education, which documented the design and refinement of a PD programme to facilitate teachers’ effective use of technology to teach mathematics.Discussion and conclusions: The examples presented and discussed here suggest how a DBR process is able to facilitate fruitful collaborations between researchers and practitioners and increase engagement in research. By working with practitioners to design interventions such as PD programmes, DBR can provide a practical approach for improving practice and deepening the relationship between educational research and classroom practice.
EdTechHub.Copy: 2129771:XWT48UG5 shortDOI: 10/ggd8hp KerkoCite.ItemAlsoKnownAs: 10.1080/00131881.2019.1677168 10/ggd8hp 2129771:XWT48UG5 2339240:FNGCAY8H 2405685:SXE25TP7
Keywords: Design-based research; evidence-informed practice; practice; practitioners; professional development; teacher education

Mobile literacy among Syrian refugee women teachers - Bradley, Linda; Bahous, Rima; Albasa, Ali (CALL and complexity – short papers from EUROCALL 2019, 2019)
This research project investigates mobile literacy of Syrian refugee women teachers settled in Lebanon and Sweden. Our research provides input into Syrian refugee women teachers' professional aspirations and their connection to informal mobile learning. In both countries, training programs are used for these newly arrived teachers, enabling them to move forward in their careers, where digital and mobile learning play an important part. The purpose is to investigate how Syrian refugee women teachers are blending their teaching profession and vocational training with mobile literacy and digital technology. A qualitative method approach was applied, interviewing 20 refugee women in Lebanon and Sweden, all teachers from Syria. The outcomes show that the teachers are developing their vocational abilities in getting more career-oriented training in their areas of education by means of enhancing their language skills through mobile technology. [For the complete proceedings, see ED600837.]
Publisher: Research-publishing.net, La Grange des Noyes, 25110 Voillans, France KerkoCite.ItemAlsoKnownAs: 10.14705/rpnet.2019.38.986 2339240:ZAUCKJ67 2405685:45VMGDEX 2405685:8RNRFPG7 2405685:HUEZG3W8 2534378:93K5R9FV 2534378:NR6VFNNC
Keywords: Career Development; Cross Cultural Studies; ERIC; Resources in Education (RIE); Faculty Development; Females; Foreign Countries; Handheld Devices; Informal Education; Information Technology; Land Settlement; Lebanon; Literacy; Occupational Aspiration; Refugees; Second Language Instruction; Second Language Learning; Sweden; Syria; Teacher Attitudes; Telecommunications; Videoconferencing; __:import:01; __:match:final; __:matched; __:study_id:2095768; ___working_potential_duplicate; __finaldtb

Hello, I’m Björn, Director of Research – The EdTech Hub - Haßler, Björn (EdTech Hub, 2019)
I’m Dr Björn Haßler, one of the three Directors of Research for the programme. Research, and particularly at-scale research, is a core focus for the #EdTechHub and that’s why we have three Directors of Research, who will also introduce themselves. I am — we all are — extremely happy that we have been awarded the programme. We, like all our competitors, worked hard for around 1.5 years until the final submission. However, this work paid off! It means we can get going on the important mission.
EdTechHub.Copy: 2129771:NPLNWHCZ shortDOI: 10/ghgnfd KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906829 10/ghgnfd 2129771:NPLNWHCZ 2129771:XKQV2EDS 2405685:3IM8DBXI
Keywords: _DOILIVE; _EdTechHub_Output; _yl:r; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Coherence and the positioning of teachers in professional development programs. A systematic review - Lindvall, Jannika; Ryve, Andreas (Educational Research Review, 2019)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.edurev.2019.03.005 2339240:T6FJICU7 2405685:NECFNMUF
Keywords: Important; Read

Coherence and the positioning of teachers in professional development programs. A systematic review - Lindvall, Jannika; Ryve, Andreas (Educational Research Review, 2019)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.edurev.2019.03.005 2405685:UXEQSP6H 2534378:R7UFM8RT
Keywords: Important; Read

Coherence and the positioning of teachers in professional development programs. A systematic review - Lindvall, Jannika; Ryve, Andreas (Educational Research Review, 2019)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.edurev.2019.03.005 2339240:T6FJICU7 2405685:NECFNMUF
Keywords: Important; Read

WhatsApp: Creating a virtual teacher community for supporting and monitoring after a professional development programme - Moodley, Maglin (South African Journal of Education, 2019)
KerkoCite.ItemAlsoKnownAs: 10.15700/saje.v39n2a1323 2339240:R7L9J4C3 2405685:HSIJJWM4

Five starting points on innovation for the EdTech Hub – The EdTech Hub - Simpson, Lea (EdTech Hub, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:XCJNWSVR XCJNWSVR
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

English language teaching in Bangladesh today: Issues, outcomes and implications - Rahman, Mohammad Mosiur; Islam, Md Shaiful; Karim, Abdul; Chowdhury, Takad Ahmed; Rahman, Muhammad Mushfiqur; Seraj, Prodhan Mahbub Ibna; Singh, Manjet Kaur Mehar (Language Testing in Asia, 2019)
Given the significance of English in the global world, English language teaching in Bangladesh has become subject to a supreme concern in maintaining economic growth and developing a skilled workforce. In this article, several barriers have been discussed based on a critical analysis of published materials. This review article covers several key issues such as the status of English in the country; English in education policies; factors affecting the implementation of communicative language teaching curriculum, method, and materials in Bangladesh; validity of the current assessment and its washback effect on English language teaching in Bangladesh; and current situation of teachers’ professional development. The article concluded with language policy and planning implications for policymakers, curriculum and material developers, public exams’ test-setters, and future English teacher training programmes, keeping the overall development of ELT in Bangladesh in mind.
KerkoCite.ItemAlsoKnownAs: 10.1186/s40468-019-0085-8 10/gg398d 2339240:6DJW9B5P 2339240:T5V5WJQJ 2405685:EH4KT3RK 2405685:VUKTNAHY

Learning ecologies through a lens: Ontological, methodological and applicative issues. A systematic review of the literature - Sangrá, Albert; Raffaghelli, Juliana Elisa; Guitert‐Catasús, Montse (British Journal of Educational Technology, 2019)
The concept of learning ecologies emerged in a context of educational change. While the “learning ecologies” construct has offered a broad semantic space for characterizing innovative ways of learning, it is also true that its potential to promote innovative educational interventions may have been hindered by this same broadness. Based on this assumption, in this paper the authors carried out a systematic review of the literature on learning ecologies with the aim of analysing: (1) the varying definitions given to the concept, including the ontological perspective underlying the phenomena studied; (2) the methodological approaches adopted in studying the phenomenon; and (3) the applications of the research on this topic. Throughout this analysis, the authors attempt to describe the criticalities of the existing research, as well as the potential areas of development that align well with the theoretical/ontological issues, methodological approaches and educational applications. The authors selected and analysed 85 articles, which they then classified in a set of 20 categories defined by them on a theoretical basis. Moreover, in order to triangulate the manual coding, a bibliometric map was created showing the co-citation activity of the 85 papers. The emerging picture showed significant variability in the ontological definitions and methodological approaches. In spite of this richness, few educational applications currently exist, particularly with regard to technology-enhanced learning developments. Most research is observational, devoted to describing hybrid (digital and on-site) learning activities that bridge the gap between the school and social spaces. Furthermore, many of the studies relate to the field of secondary education, with fewer studies exploring adult learning and higher education. The studies dealing with professional development relate mostly to teachers’ continuing education. The authors conclude that the concept of learning ecologies could be used to address further experimental and design-based research leading to research applications if there is proper alignment between the ontological, methodological and applicative dimensions. The main potential of this strategy lies in the possibility of supporting learners by raising their awareness of their own learning ecologies, thereby empowering them and encouraging them to engage in agentic practices. This empowerment could help maintain and build new and better learning opportunities, which every learning ecology can incorporate, amidst the chaotic abundance that characterizes the digital society.
shortDOI: 10/gf5f7h KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12795 10/gf5f7h 2339240:B3XDZLNT 2405685:64NV5INX
Keywords: Reviewed